GIC-LAC Project: Strengthening mitigation objectives and reducing emissions in LAC agrifood systems - Yomayuza Herrera, Karoll Valentina; Sylvester, Janelle Marie (2025)
The project "Strengthening national mitigation objectives and opening a path to reduce emissions in agrifood systems in Latin America and the Caribbean" #GICLAC is funded by the New Zealand Government and implemented by the Alliance of Bioversity International and the International Centre for Tropical Agriculture, seeks to transform the region's agrifood systems by developing technical capacities in countries to improve the reporting of greenhouse gas emissions, promoting inventories that are transparent, consistent, and technically robust.